Heparanase inhibitor improves clinical study in patients with septic cardiomyopathy - Chen, Di; Li, Honglei; Huang, Shitao; Huang, Zhongya; Sun, Yibo; Liu, Liping (Frontiers in Medicine, 2024)
Main content of the article:Septic cardiomyopathy (SCM) is a common and serious complication in patients with sepsis and septic shock. Due to its complex pathogenesis, there are currently no clear diagnostic criteria. Clinical treatment mainly focuses on correcting the underlying disease and providing symptomatic relief, with the mortality rate remaining high. This study aims to investigate the impact of low molecular weight heparin on the levels of Heparanase (HPA) in SCM patients and evaluate the clinical diagnostic value of HPA in SCM patients. The author likes the style of articles in this journal very much, and often reads many of them. I hope you can give me valuable comments